(untitled) (Al-Qamar, 2021)
This research paper is a brief overview of the explanation of Ayesha’s scholarly position. It is undoubted fact that Hazrat Ayesha was a great scholar and intellectual of Islam. She was not only the first lady of Islam but also acquired privilege over various companions of Prophet due to her prior position. She was also superior to many male companions because of his scholarly status. This research paper makes it clear that Hazrat Ayesha is regarded as a mujtahid and her scholarly services are enviable. She was the witness to the scientific progress and innumerable events that took place in the early days of Islam. She possessed the highest memory including education and training, knowledge and grace, speech, oratory, linguistics. Her scholarly position can also be gauged from his narration of hadith. Sheikhs agree on many of them She was a very brave lady of Islam and she led the expedition of the battle of Jumal in 36 A.H. This research paper highlights the scholarly position of Hazrat Ayesha and her scholarly services.